2011
DOI: 10.1155/2011/824162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Flooding on the Oviposition Capacity of Engorged Adult Females and Hatchability of Eggs of Dog Ticks:Rhipicephalus sanguineusandHaemaphysalis leachi leachi

Abstract: Effects of water flooding on the oviposition capacity of engorged adult females and hatchability of eggs of Rhipicephalus sanguineus and Haemaphysalis leachi leachi under laboratory conditions were investigated. The durations of time of water flooding were 1, 2, 4, 6, 12, 24, 48, 72, 96, and 120 hours. Engorged females of R. sanguineus and H. leachi leachi did not oviposit after being flooded for more than 48 and 6 hours, respectively. The preoviposition periods of both species were longer than those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Therefore, one can speculate that the driving effect of rainfall on DIN is probably driven by the effect of rainfall on nymph abundance. This association may be related to the effect of rainfall on tick oviposition rates [ 65 ], number of eggs per clutch and/or hatching success rather than on questing activity [ 66 ], since heavy rain silts up egg masses [ 67 ]. Therefore, some climatic factors during peak months of egg deposition could be critical for subsequent distribution of ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one can speculate that the driving effect of rainfall on DIN is probably driven by the effect of rainfall on nymph abundance. This association may be related to the effect of rainfall on tick oviposition rates [ 65 ], number of eggs per clutch and/or hatching success rather than on questing activity [ 66 ], since heavy rain silts up egg masses [ 67 ]. Therefore, some climatic factors during peak months of egg deposition could be critical for subsequent distribution of ticks.…”
Section: Discussionmentioning
confidence: 99%
“…The climatic factors during the month of egg deposition will probably be critical for the distribution of ticks, as there would not be sustainable tick population if the eggs do not survive and hatch. The effect of flooding upon the dog ticks ( Rhipicephalus sanguineus and Haemaphysalis leachi leachi ) shows that flooding affected oviposition, reduced the number of eggs laid and the percentage of hatchability [ 56 ]. It has been suggested that heavy rain silts up the egg masses [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant change in laying pattern between Solution E and F treated ticks was observed and, in most cases,mortality was not seen until 11 th day post treatment. Start of mortalities 11 th day post treatment suggests a possibility that if the ticks are left in control solution more than two minutes used in AIT, death and better oviposition inhibition can be achieved [42].…”
Section: Egypt J Vet Sci Vol 51 No 2 (2020)mentioning
confidence: 99%